People's Business Credit, Capital Management, and Spiritual Value in Improving MSMEs Performance - Septia Zenniar; Suriani Suriani (Al-Amwal : Jurnal Ekonomi dan Perbankan Syari'ah, 2023)
This study aimed to investigate the influence of business credit, management capital, and spiritual values on the performance of micro, small, and medium-sized enterprises (MSMEs) in the Teunom sub-district. Multiple linear regression analysis was used as the quantitative method for this research. The research population included 115 respondents who were SMEs and KUR recipients at BSI KCP Teunom, and data were collected through a questionnaire. The findings revealed that people's business credit and spiritual values had a significant and positive impact on the performance of MSMEs. However, management capital did not affect the performance of MSMEs. The study strongly suggests that increasing the religiosity value of the community towards the funds received could lead to an increase in people's business loans.InsertRephraseImprove itShorten itSound confidentMoreÂ